Evaluacion comparativa en la etapa de germinacion de dos variedades de aguacate (persea americana mill) con la utilización de tres métodos de escarificaciòn, con dos tipos de sustratos para la obtencion de plantulas en Rumipamba Central del canton Salcedo - Barrionuevo Bassante, Miguel Fernando (2015)
This research was: COMPARATIVE EVALUATION IN THE STAGE OF GERMINATION OF TWO VARIABLES OF AVOCADO (PERSEA AMERICANA MILL BY USING OF THREE METHODS OF SCARIFICATION, WITH TWO TYPES OF SUBSTRATE TO OBTAIN SEEDLINGS IN RUMIPAMBA CENTAL OF SALCEDO CANTON, at 2630 m.o.s.l. and fulfilled the objectives; Identify the best method of scarification; Determine the best substrate; Identify the best variety. Factors in study were: Factor A substrates: (S1: prepared) (S2_lambert); Factor B: scarification: (M1 = immersion in hot water 50 ° per minute), (M2 = mechanical scarification), (M3 = immersion + cross-section), (M4 = control without scarification). Factor C: avocado variety: (V1 = national avocado), (V2 = Guatemalan - Hass). The experimental design that applied was split plot with 4x2 factorial with three replications arrangement. Tests of significance of Tukey 5% was used. These used 960 avocado seeds distributed in 48 experimental units which were submitted to the aforementioned factors in study, irrigation was performed by spraying while maintaining the ability to field....